HUBUNGAN ANTARA PENGETAHUAN DENGAN KECEMASAN PASIEN SEBELUM TINDAKAN KATETERISASI JANTUNG DI MAYAPADA HOSPITAL TANGERANG - Ita ike Ratnasari; Retno Andriati; Ayu Rahayu; Dyna Mei Lolita Sirait; Marsondang Situmeang; Rina Asih Pratiwi (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Knowledge is obtained through human sensory perception, particularly hearing and sight, and plays an important role in shaping individuals’ understanding of health conditions. Patient anxiety prior to cardiac catheterization is one of the factors that may affect psychological readiness. This study aimed to examine the relationship between the level of knowledge and patient anxiety before undergoing cardiac catheterization at Mayapada Hospital Tangerang. This study employed a correlational design with a cross-sectional approach. The population consisted of all patients scheduled for elective cardiac catheterization, with a total sample of 30 patients selected using total sampling. Data were collected using knowledge and anxiety questionnaires and analyzed using the chi-square test. The results showed that there was no significant relationship between the level of knowledge and patient anxiety prior to cardiac catheterization (p = 0.282; p > 0.05). In conclusion, the level of knowledge was not associated with patient anxiety before cardiac catheterization, indicating that anxiety may be influenced by other factors. Further studies are recommended to explore other factors that may affect patient anxiety prior to cardiac catheterization.